Identification of an Alarm Pheromone-Binding Chemosensory Protein From the Invasive Sycamore Lace Bug Corythucha ciliata (Say) - Li, Fengqi; Fu, Ningning; Li, Du; Chang, Hetang; Qu, Cheng; Wang, Ran; Xu, Yihua; Luo, Chen (Frontiers in Physiology, 2018)
The spread of the exotic insect pest sycamore lace bug Corythucha ciliata (Say) is increasing worldwide. The identification of behaviorally active compounds is crucial for reducing the current distribution of this pest. In this study, we identified and documented the expression profiles of genes encoding chemosensory proteins (CSPs) in the sycamore lace bug to identify CSPs that bind to the alarm pheromone geraniol. One CSP (CcilCSP2) was found to be involved in the binding of geraniol, the alarm pheromone of this pest. This finding was confirmed by fluorescence competitive binding assay. We further discovered one candidate chemicals that bound to CcilCSP2 with even higher affinity than geraniol. Behavioral assays revealed that among these compounds, phenyl benzoate, similar to geraniol, significantly repelled sycamore lace bug nymphs but had no activity towards adults. This study has revealed a novel repellent compound behavioral regulation, and our findings will be beneficial for understanding the olfactory recognition mechanism of sycamore lace bug and developing a push-pull system to manage this pest in future.